The diagnostic value of salivary cortisol and salivary cortisone in patients with suspected hypercortisolism - Berndt, Vendela; Dahlqvist, Per; de Verdier, Jennie; Ryberg, Henrik; Ragnarsson, Oskar (Frontiers in Endocrinology, 2022)
Background: Diagnosing endogenous hypercortisolism remains a challenge, partly due to a lack of biochemical tests with good diagnostic accuracy. Objectives: To evaluate the diagnostic value of salivary cortisol and cortisone in patients with suspected hypercortisolism. Methods: Retrospective study including 155 patients with adrenal incidentaloma, and 54 patients with suspected Cushing´s syndrome (CS). Salivary samples were collected at home, at 11 p.m., and at 8 a.m. following an over-night dexamethasone suppression test (DST). Salivary cortisol and cortisone were measured with liquid chromatography-tandem mass spectrometry. Results: Ten of 155 patients with adrenal incidentaloma were considered to have autonomous cortisol secretion (ACS). Using previously established cut-offs, all patients with ACS had elevated plasma-cortisol (>50 nmol/L) following DST, 9/10 had elevated late-night salivary cortisone (>15 nmol/L) whereas only 4/10 had elevated late-night salivary cortisol (LNSC; >3 nmol/L) compared to 35%, 9% and 8%, respectively, of the 145 patients with non-functioning adrenal incidentaloma. Six (60%) patents with ACS had elevated salivary cortisol and cortisone at 8 a.m. following DST compared to 9% and 8%, respectively, of patients with non-functioning adrenal incidentaloma. One of 6 patients with overt CS had a normal LNSC and one had normal late-night salivary cortisone, while all had increased salivary cortisol and cortisone following DST. Conclusion: LNSC is not sufficiently sensitive or specific to be used for screening patients with suspected hypercortisolism. Instead, late-night salivary cortisone seems to be a promising alternative in patients with adrenal incidentaloma and salivary cortisone at 8 a.m. following DST in patients with suspected CS. Larger studies are needed to confirm these findings.